2019
DOI: 10.15171/jhp.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Protective and anti-inflammatory effects of silymarin on paraquat-induced nephrotoxicity in rats

Abstract: Oral administration of silymarin could ameliorate renal histopathological changes in paraquat-induced nephrotoxicity. Also, it reduced serum urea, creatinine, protein carbonyl, and malondialdehyde. Silymarin has anti-inflammatory, nephro-protective and anti-oxidative stress activities. Hence, it might be useful in patients who were exposed to nephrotoxic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Vitamin C is an important nonenzymatic antioxidant known to protect cells of the body against oxidants. The inclusion of vitamin C as one of the supplements in the present study was due to previous reports which indicated that PQ and some xenobiotics induce low vitamin C levels, and this causes renal toxicity [28,29]. The present study shows that vitamin C treated group presented significantly reduced MDA, urea, creatinine, uric acid, triacylglyceride, and LDL-cholesterol.…”
Section: Discussionsupporting
confidence: 57%
“…Vitamin C is an important nonenzymatic antioxidant known to protect cells of the body against oxidants. The inclusion of vitamin C as one of the supplements in the present study was due to previous reports which indicated that PQ and some xenobiotics induce low vitamin C levels, and this causes renal toxicity [28,29]. The present study shows that vitamin C treated group presented significantly reduced MDA, urea, creatinine, uric acid, triacylglyceride, and LDL-cholesterol.…”
Section: Discussionsupporting
confidence: 57%
“…Silybum marianum is a member of Asteraceae family, it is used to treat liver disease as a hepatoprotective herb. [18]. The hepatoprotective effect of silymarin is attributed to its dosedependent antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%